Paradoksi kibervesolja - Kovač, Miha (Knjižnica, 2007)
The paper analyzes the failure of predictions from mid-nineties that an e-book will become more popular than a printed book. The author stresses that the reasons for this failure are predominantly economical and sociological and have much less to do with technological failures of e-book reading devices that it is popularly believed. The backbone of the book publishing process is the inseparable link between the content and its carrier; on this basis, the publishers has become the gatekeepers of intellectual production and the authorship has become a profession. In e-publishing, the link between the content and its carrier disintegrated; as a consequence, e-book publishing never established itself in a form of successful business process. Additionally, throughout the last 500 years, the printed book established itself as the most appropriate media for dissemination and storage of the most sophisticated product of human mind. The paper shows that the e-book lacks the necessary features to substitute printed book in this role. However, regardless its dominance over e-book, the production and marketing of printed books have become almost entirely digitized. As a consequence, instead of e-book readers, paper has become the most important carrier of e-book content.
Keywords: elektronske knjige; elektronsko založništvo; tiskanje; printing; tisk